2010
DOI: 10.1111/j.1365-2796.2009.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Worse blood pressure control in patients with cerebrovascular or peripheral arterial disease compared with coronary artery disease

Abstract: Abstract. Mechtouff L, Touzé E, Steg PG, Ohman EM, Goto S, Hirsch AT, Röther J, Aichner FT, Weimar C, Bhatt DL, Alberts MJ, Mas J-L, on behalf of the REACH Registry Investigators (Paris-Descartes University; Université Paris 7; Paris, France, Duke University, Durham NC, USA, Tokai University, Isehara, Japan, University of Minnesota, Minneapolis, MN, USA, Academic Teaching Hospital Hannover Medical School, Minden, Germany, Academic Teaching Hospital Wagner-Jauregg, Linz, Austria, University of Duisburg-Essen, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
(61 reference statements)
2
2
0
Order By: Relevance
“…A similar trend was found in a study based on two national registries involving primary care physicians, which demonstrated that optimal care was more frequently achieved in patients with CAD than in those with cerebral ischaemia 9 21. The reasons for such discrepancies remain hypothetical.…”
Section: Discussionsupporting
confidence: 75%
“…A similar trend was found in a study based on two national registries involving primary care physicians, which demonstrated that optimal care was more frequently achieved in patients with CAD than in those with cerebral ischaemia 9 21. The reasons for such discrepancies remain hypothetical.…”
Section: Discussionsupporting
confidence: 75%
“…Not surprisingly, the use of expensive lipid-lowering agents, most likely statins, was much higher in our study compared with the WHO-PREMISE, with over 80% of patients with coronary artery disease and 50% of those with stroke/TIA receiving such therapy. As shown elsewhere, our study shows that patients with stroke/TIA are not only less likely to be prescribed secondary prevention therapies but their BP and lipid levels are less well controlled (20,23). The observed higher prescribing in those with TIA compared with stroke may reflect the recognition by GPs that such therapy in the former group is beneficial in reducing the risk of future stroke or possibly the perception that such patients have more to gain in terms of disability-free survival (24).…”
Section: Discussionsupporting
confidence: 63%
“…ACCORD (Action to Control Cardiovascular Risk in Diabetes) trial disagreed with the results of this study conducted in diabetic patients at high cardiovascular risk and showed no difference in terms of cardiovascular outcomes between intensive antihypertensive therapy (target SBP <120 mm Hg) compared to the standard (target SBP <140 mmHg) [32]. Unfortunately, in a recent study conducted in 2010, the proportion of patients whose blood pressure was kept under control was lower among those with PAD than among those with CAD (coronary artery disease) or CVD (cerebrovascular disease) [33]. It would therefore be useful to promote a more effective blood pressure control in these patients to improve their outcomes and prevent complications primarily related to PAD.…”
Section: Modification Of Cardiovascular Risk Factorsmentioning
confidence: 94%